2021
DOI: 10.5334/pb.1106
|View full text |Cite
|
Sign up to set email alerts
|

Testing Measurement Invariance of the Dark Triad Dirty Dozen in a Belgian Adult Sample

Abstract: The Dirty Dozen (Jonason & Webster, 2010) is a frequently used concise version of the Dark Triad to measure three socially aversive personality traits: Machiavellianism, psychopathy and, narcissism. The present study has examined measurement invariance in a sample of Belgian adults. The present study aims to assess measurement invariance of the Dutch version of the Dirty Dozen measure across gender in a large city-based representative adult sample in Belgium (N = 1587). Multi-group firstorder confirmatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Several scholars have raised concerns about the use of the Dirty Dozen instrument to measure the DTT, as it would not sufficiently cover the constructs of interest (e.g., Miller et al, 2012). On the other hand, multiple studies have shown that the structure of the Dirty Dozen scale is stable across different cultural contexts and populations, and the scale appears to offer a reasonable trade-off between efficiency and accuracy (De Buck et al, 2021; Rogoza et al, 2021). To account for these limitations in our measures, future research should further disentangle the processes between self-control, DTT, and CDA perpetration by using more elaborate measurements and by accounting for the multidimensional nature of the study constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have raised concerns about the use of the Dirty Dozen instrument to measure the DTT, as it would not sufficiently cover the constructs of interest (e.g., Miller et al, 2012). On the other hand, multiple studies have shown that the structure of the Dirty Dozen scale is stable across different cultural contexts and populations, and the scale appears to offer a reasonable trade-off between efficiency and accuracy (De Buck et al, 2021; Rogoza et al, 2021). To account for these limitations in our measures, future research should further disentangle the processes between self-control, DTT, and CDA perpetration by using more elaborate measurements and by accounting for the multidimensional nature of the study constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Supported by the three factor solution found in our sample, we decided to approach the Dark Triad as separate traits as this allowed us to pinpoint detailed differences in how the different strategies these traits represent may be linked to sexual harassment experiences in different relationship types. We chose the Dirty Dozen questionnaire to measure the Dark Triad traits, as its structure appears to be stable across different cultural contexts and populations and seems to provide a reasonable trade-off between efficiency and accuracy (De Buck et al, 2021; Rogoza et al, 2021). Lastly, we argue that a “separatist” approach to these three traits is further justified by our finding that different dark personality traits were uniquely linked to sexual harassment experiences depending on the type of relationship.…”
Section: Discussionmentioning
confidence: 99%